Reproductive ecology of the glacier lanternfish Benthosema glaciale - García Seoane, Eva; Bernal, A.; Saborido-Rey, Fran (Hydrobiologia, 2014)
13 páginas, 4 tablas, 6 figuras Myctophids play a key role in the transfer of energy in pelagic food webs, linking zooplankton to higher trophic levels. Data are presented, for the first time for the glacier lanternfish (Benthosema glaciale), on maturity ogives, size-at-maturity and reproductive strategy in terms of ovarian organization and fecundity type in two contrasting environments: North Atlantic and Mediterranean. We analysed 292 females collected in Flemish Cap during early summer 2009 and 2011 and off the Balearic Islands during late autumn 2009 and early summer 2010. The spawning season differed between areas. Size at 50% maturity in Flemish Cap was 47.6 and 49.1 mm in 2009 and 2011, respectively, but significantly smaller, 24.5 mm, in the Balearic sea. B. glaciale is a batch spawner with asynchronous ovarian development and indeterminate fecundity. Batch fecundity showed significant relationships with length and weight, although average relative batch fecundity was low (1031 ± 396 oocytes/gram). We compared two staining techniques: Hematoxylin–eosin and PAS–hematoxylin–metanil yellow with the latter being more useful to detect mature females and spawning indicators in regressing and regenerating females. Our results contribute to a better understanding of the reproductive potential and ecological role of this species, the most abundant myctophid in the northern Atlantic. This study was possible thanks to a JAE Predoctoral Fellowship of the CSIC co-financed by the European Social Fund and thanks to the collaboration of the project IDEADOS (CTM2008-04489-C03-02) given by the Spanish Science and Innovation Ministry and of the Program for the Data Collection in the Fisheries Sector from the European Commission and CSIC. Peer reviewed